2016
DOI: 10.5500/wjt.v6.i2.411
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of new expanded selection criteria using total tumor size and18F-fluorodeoxyglucose - positron emission tomography/computed tomography for living donor liver transplantation in patients with hepatocellular carcinoma: The National Cancer Center Korea criteria

Abstract: AIM:To expand the living donor liver transplantation (LT) pool of eligible patients with hepatocellular carcinoma (HCC) using new morphological and biological criteria. METHODS: RESULTS:We enrolled a total of 280 patients who pathologically confirmed to have HCC and performed the PET/CT before transplantation. Among them, 164 (58.6%) patients fulfilled the NCCK criteria and 132 patients (47.1%) met the Milan criteria. Five-year overall and disease-free survival rates for patients who fulfilled the NCCK criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 34 publications
0
64
0
Order By: Relevance
“…Another potential selection criterion for patients beyond Milan criteria, especially in LT centers with either short LT wait times or prior to live donor liver transplant (LDLT), is to use 18 F‐FDG‐PET scans, an excellent predictor of worse tumor differentiation and microvascular invasion. FDG‐negative patients beyond Milan criteria have satisfactory post‐LT outcome, whereas those with a tumor‐to‐nontumor ratio (TNR) greater than 2 tend to do poorly (Table ).…”
Section: Response To Lrt and 18f‐fdg‐petmentioning
confidence: 99%
“…Another potential selection criterion for patients beyond Milan criteria, especially in LT centers with either short LT wait times or prior to live donor liver transplant (LDLT), is to use 18 F‐FDG‐PET scans, an excellent predictor of worse tumor differentiation and microvascular invasion. FDG‐negative patients beyond Milan criteria have satisfactory post‐LT outcome, whereas those with a tumor‐to‐nontumor ratio (TNR) greater than 2 tend to do poorly (Table ).…”
Section: Response To Lrt and 18f‐fdg‐petmentioning
confidence: 99%
“…The NCCK criteria were defined as tumors with a total tumor size of 10 cm or less and negative PET status. In their study, the 5-year overall and disease-free survival rates of 164 patients within the NCCK criteria were 85.2% and 84.0%, respectively (36). The NCCK criteria increased the number of candidates suitable to LT by 24% compared with the Milan criteria, while the results of the NCCK were not inferior to those of the Milan criteria (36).…”
Section: Expanded Korean Criteria For Lt For Hccmentioning
confidence: 97%
“…According to the NCCK criteria, the PET positivity was assessed by experienced nuclear medicine physicians who checked that the maximal standard uptake value of a tumor (T max ) was higher than that of surrounding noncancerous liver tissue (L max ) (T max /L max > 1.0) (36). On the other hand, Lee et al (38) reported that a T max /L max value >1.15 was the most effective predictor of HCC recurrence after LT.…”
Section: Expanded Korean Criteria For Lt For Hccmentioning
confidence: 99%
“…In 2015, Lee et al 44 published a study including 280 patients who received LDLT at the National Cancer Center and reported that HCC patients exceeding the Milan criteria with a negative PET/CT and overall tumor size <10 cm demonstrated overall survival and recurrence-free survival rates similar to those meeting the Milan criteria. In 2016, they proposed the so-called National Cancer Center Korea (NCCK) criteria, according to which patients selected for LDLT should present with negative PET/ CT assessment and a total tumor size < 10 cm 45 .…”
Section: Ncck Criteriamentioning
confidence: 99%
“…Significantly, PET-positive findings were the only independent factor predictive of cancer-related patient drop-out from the waiting list. On this basis, Lee et al 45 proposed the aforementioned NCCK criteria.…”
Section: Tumor Biology: Anaspect To Be Included In the Criteriamentioning
confidence: 99%